Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor (Journal of Agricultural and Food Chemistry, 2009)
Phenolic compounds, namely, hydrolyzable tannins and low molecular weight phenolic compounds, were isolated and purified from Portuguese cork from Quercus suber L. Some of these compounds were studied to evaluate their antioxidant activity, including free-radical scavenging capacity (DPPH method) and reducing capacity (FRAP method). All compounds tested showed significant antioxidant activity, namely, antiradical and reducing properties. The antiradical capacity seemed to increase with the presence of galloyl groups. Regarding the reducing capacity, this structure-activity relationship was not so clear. These compounds were also studied to evaluate the growth inhibitory effect on the estrogen responsive human breast cancer cell line (ERþ) MCF-7 and two other colon cancer cell lines (Caco-2 and HT-29). Generally, all the compounds tested exhibited, after a continuous exposure during a 48 h period, a dose-dependent growth inhibitory effect. Relative inhibitory activity was primarily related to the number of phenolic hydroxyl groups (galloyl and HHDP moieties) found in the active structures, with more groups generally conferring increased effects, except for HHDP-di-galloyl-glucose. Mongolicain B showed a greater potential to inhibit the growth of the three cell lines tested, identical to the effect observed with castalagin. Since these compounds are structurally related with each other, this activity might be based within the C-glycosidic ellagitannin moiety.
From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 19888728
Keywords: antioxidants; Antioxidants: chemistry; Antioxidants: isolation & purification; Antioxidants: pharmacology; Antitumor activity; Cell Line; Cell Proliferation; Cell Proliferation: drug effects; Cork; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: chemistry; Hydrolyzable Tannins: isolation & purification; Hydrolyzable Tannins: pharmacology; phenolic compounds; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: isolation & purification; Plant Extracts: pharmacology; Quercus; Quercus suber L.; Quercus: chemistry; Tumor

Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor (Journal of Agricultural and Food Chemistry, 2009)
Phenolic compounds, namely, hydrolyzable tannins and low molecular weight phenolic compounds, were isolated and purified from Portuguese cork from Quercus suber L. Some of these compounds were studied to evaluate their antioxidant activity, including free-radical scavenging capacity (DPPH method) and reducing capacity (FRAP method). All compounds tested showed significant antioxidant activity, namely, antiradical and reducing properties. The antiradical capacity seemed to increase with the presence of galloyl groups. Regarding the reducing capacity, this structure-activity relationship was not so clear. These compounds were also studied to evaluate the growth inhibitory effect on the estrogen responsive human breast cancer cell line (ERþ) MCF-7 and two other colon cancer cell lines (Caco-2 and HT-29). Generally, all the compounds tested exhibited, after a continuous exposure during a 48 h period, a dose-dependent growth inhibitory effect. Relative inhibitory activity was primarily related to the number of phenolic hydroxyl groups (galloyl and HHDP moieties) found in the active structures, with more groups generally conferring increased effects, except for HHDP-di-galloyl-glucose. Mongolicain B showed a greater potential to inhibit the growth of the three cell lines tested, identical to the effect observed with castalagin. Since these compounds are structurally related with each other, this activity might be based within the C-glycosidic ellagitannin moiety.
From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)
Keywords: antioxidants; Antioxidants: chemistry; Antioxidants: isolation & purification; Antioxidants: pharmacology; Antitumor activity; Cell Line; Cell Proliferation; Cell Proliferation: drug effects; Cork; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: chemistry; Hydrolyzable Tannins: isolation & purification; Hydrolyzable Tannins: pharmacology; phenolic compounds; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: isolation & purification; Plant Extracts: pharmacology; Quercus; Quercus suber L.; Quercus: chemistry; Tumor

Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco a (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)
Keywords: Animal; Animals; bile; bioavailability; Biological Availability; Body Fluids; Body Fluids: chemistry; Cereals; Cereals: chemistry; colon; diet; ellagic acid; Ellagitannin; gall bladder; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: metabolism; Hydrolyzable Tannins: pharmacokinetics; intestine; metabolism; Models; Quercus; Seeds; Seeds: chemistry; Swine; Swine: metabolism; Tissue Distribution; urolithin

Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I.; Tomás-Barberán, Francisco a (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 17990850
Keywords: Animal; Animals; bile; bioavailability; Biological Availability; Body Fluids; Body Fluids: chemistry; Cereals; Cereals: chemistry; colon; diet; ellagic acid; Ellagitannin; gall bladder; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: metabolism; Hydrolyzable Tannins: pharmacokinetics; intestine; metabolism; Models; Quercus; Seeds; Seeds: chemistry; Swine; Swine: metabolism; Tissue Distribution; urolithin

Determination of Poly(ethylene glycol)-Binding to Browse Foliage, as an Assay of Tannin, by Near-Infrared Reflectance Spectroscopy - Landau, Serge; Dvash, Levana; Decandia, Mauro; Cabiddu, Andrea; Shapiro, Fira; Molle, Giovanni; Silanikove, Nissim (Journal of Agricultural and Food Chemistry, 2004)
Nutritionists are interested in functional assays of tannins that do not require time-consuming and expensive extraction, such as the 14C-labeled poly(ethylene glycol) (PEG)-binding (PEG-b) assay. This paper reports the application of near-infrared (NIR) spectroscopy to determine the percentage of PEG binding, in place of the 14C-labeled PEG-b assay of tannin, in Mediterranean woodland vegetation. Calibration was done with 53 samples from 14 species and was validated on 25 samples from 10 species. PEG-b ranged between 1.4 and 20.7% in the samples. The calibration obtained by using the modified partial least-squares (MPLS) method, with all wavelengths in the 1100?2500 nm range combined, and the validation were reasonably linear (R?2 = 0.96 and 0.91, respectively). The accuracies, estimated from the standard errors of cross-validation and prediction, were ±1.6 and ±1.7% PEG-b, respectively. The NIRS-aided procedure proposed here can serve as an accurate, inexpensive, time-saving, and environment-friendly functional assay of tannin in Mediterranean browse. Keywords: NIRS; goats; nutrition; poly(ethylene glycol); pasture
From Duplicate 1 (Determination of Poly(ethylene glycol)-Binding to Browse Foliage, as an Assay of Tannin, by Near-Infrared Reflectance Spectroscopy - Landau, Serge; Dvash, Levana; Decandia, Mauro; Cabiddu, Andrea; Shapiro, Fira; Molle, Giovanni; Silanikove, Nissim)
Keywords: Animal Nutritional Physiological Phenomena; Animals; Carbon Radioisotopes; Fabaceae; Fabaceae: chemistry; Goats; Hydrolyzable Tannins; Hydrolyzable Tannins: analysis; Near-Infrared; NIRS; nutrition; pasture; poly(ethylene glycol); Polyethylene Glycols; Polyethylene Glycols: metabolism; Spectroscopy

Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila (Journal of Agricultural and Food Chemistry, 2003)
The gastroprotective effects of 70% acetone extracts of Quercus suber and Quercus coccifera leaves and of tannins (pedunculagin, castalagin, phillyraeoidin A, and acutissimin B) purified from these extracts were examined in the mouse using the ethanol-induced gastric ulcer model. Both extracts (25, 50, and 100 mg/kg), given orally, prevented the formation of ethanol-induced lesions in the stomach. The percent protection varied between 68 and 91%. Purified tannins (50 mg/kg) were also effective in protecting the stomach against ethanol, and the percent protection varied from 66 to 83%. Castalagin was the most potent. Both extracts and all of the tannins tested (10, 25, and 50 ?g/mL) strongly inhibited (55?65%) the lipid peroxidation of rabbit brain homogenate. These results suggest that the gastroprotective effects of extracts of Q. suber and Q. coccifera leaves and the purified tannins in this experimental model are related to their anti-lipoperoxidant properties. Keywords: Experimental gastric ulcer; lipid peroxidation; medicinal plants; Quercus sp.; tannins; castalagin
From Duplicate 2 (Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila)
Keywords: Acetone; Animals; Biphenyl Compounds; castalagin; Catechols; Catechols: therapeutic use; Ethanol; Experimental gastric ulcer; Hydrolyzable Tannins; lipid peroxidation; Lipid Peroxidation: drug effects; Male; Medicinal plants; Mice; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: therapeutic use; Plant Leaves; Plant Leaves: chemistry; Quercus; Quercus sp.; Quercus: chemistry; Rabbits; Stomach Ulcer; Stomach Ulcer: chemically induced; Stomach Ulcer: prevention & control; Tannins; Tannins: pharmacology; Tannins: therapeutic use